Enhanced and synergistic downregulation of oncogenic miRNAs by self-assembled branched DNA - Nahar, S.; Nayak, A. K.; Ghosh, A.; Subudhi, U.; Maiti, S. (Nanoscale, 2018)
miRNAs, a group of small non-coding RNA molecules, regulate the expression of many genes involved in various cellular processes. Acute evidence suggests that one miRNA can regulate many genes as its targets, while one gene can be targeted by many miRNAs that co-operatively regulate the gene. Thus, targeting a single miRNA is not sufficient enough to rescue the disease phenotype but it is also essential to target multiple miRNAs simultaneously. This inspired us to design a novel DNA nanostructure that can concurrently downregulate multiple oncomiRNAs. Here we designed a programmable antimiR branched DNA (antimiR-bDNA) nanostructure having antimiRNAs for selective binding to oncomiRNAs miRNA-27a, 96 and 182 which collectively downregulate FOXO1a expression. The antimiR-bDNAs show enhanced stability compared to naked antimiRNAs in serum and are able to knockdown these miRNAs with up to similar to 50% greater repression as compared to antimiRNAs. This synergistic miRNA repression leads to the restoration of FOXO1a protein levels which in turn inhibit G1-S traversion in cancer cells. To the best of our knowledge, this is the first study harnessing the ability of bDNA structures to silence multiple miRNAs simultaneously.

Screening of osmotic stress-tolerant bacteria for plant growth promotion in wheat (Triticum aestivum L.) and brinjal (Solanum melongena L.) under drought conditions - Patel, P.; Patil, T.; Maiti, S.; Paul, D.; Amaresan, N. (Letters in Applied Microbiology, 2022)
Drought stress adversely affects plant growth and productivity. Therefore, the application of plant growth-promoting bacteria is a viable option for combating drought resistance in crops. In this study, 144 bacteria were isolated from the Kutch desert soil in Gujarat. Based on osmotic stress tolerance and PGP properties, two strains, Bacillus tequilensis (KS5B) and Pseudomonas stutzeri (KS5C) were tested for their effect on wheat (Triticum aestivum L.) and brinjal (Solanum melongena L.) under drought stress conditions. Inoculation with osmotic stress-tolerant bacteria showed 15 center dot 15-29 center dot 27% enhancement in root length of wheat and 15 center dot 27-32 center dot 59% in brinjal plants. Similarly, the enhancement of shoot length ranged from 14 center dot 72 to 37 center dot 70% for wheat and 59 center dot 39-95 center dot 94% for brinjal plants. Furthermore, the inoculated plants showed significant improvement in chlorophyll content and antioxidant properties such as proline, peroxidase and polyphenol oxidase activity compared to the control. Therefore, the bacterial strains identified in this study can be used to mitigate drought stress and enhance plant biomass.
Keywords: Antioxidant; brinjal; drought; plant growth; Wheat